Heating Up, Backing Down: Evaluating recent climate policy progress in Canada - Mertins-Kirkwood, Hadrian (Adapting Canadian Work and Workplaces (ACW), 2019)
This is a co-publication by the Canadian Centre for Policy Alternatives (CCPA) and the Adapting Canadian Work and Workplaces to Respond to Climate Change research program (ACW). It assesses the climate policy progress of Canadian governments over the past two years with respect to long-term greenhouse gas emission reductions and concludes that positive progress in British Columbia and Quebec over the past few years is outweighed by backsliding in other provinces. The new governments in Alberta and Ontario—Canada’s two biggest carbon polluters—have reversed the climate policies of previous governments, which puts Canada’s already-unlikely national targets even further at risk. The report identifies two growing threats to climate policy progress in Canada: 1. A narrow public debate over carbon pricing is eroding political will for a more comprehensive climate policy approach. There are many other policies that are less controversial and can be just as effective at reducing emissions. 2. Canadian governments have been unwilling to introduce supply-side energy policies designed to restrict the production of fossil fuels, even though keeping much of our oil and gas in the ground is necessary to avoid the worst effects of global climate breakdown. Adapting Canadian Work and Workplaces to Respond to Climate Change